Including children with autism: overcoming the challenge of integration. - Hussin, S.; Loh, S.C.; Quek, A.H. (2008)
In Malaysia, children with special needs have the opportunity for education in the special schools as well as in the integrated programme and inclusion programme conducted in the mainstream primary and secondary schools. Children who benefited from the integrated and inclusion programmes included those with autism alongside with many other categories of special needs. Children from the integrated programme who are high functioning have the privilege to be included in the mainstream classes. Many questions remain, however, about how to best implement inclusion programme in the Malaysian schools. As such, the challenge of integration remains! This paper seeks to discuss the smart initiatives since year 2005 till present by the Malaysian Government and the Non-Governmental Organisation in overcoming the challenge of integrating children with autism into the mainstream classes. A research visit was conducted as part and parcel of a major research entitled ‘Special Education for Energetic Development (SEED). The aim of the visit was to gather insight on the successful inclusion of children with autism into the mainstream classes in one of the primary schools located at the metropolitan of Kuala Lumpur, at Klang Valley. Few key features towards successful inclusion such as smart collaboration, co-teaching, peer learning, after-school coaching and experiential learning were identified. This smart initiative has spearheaded few more inclusion programmes throughout Malaysia.